Ice and snow in the geographical names of the North-East of Russia - Yu. G. Seliverstov (Лëд и снег, 2015)
The place names related to snow and ice were revealed at the territory of Northeast of Russia. The processes and phenomena connected with snow and ice were also accounted for. The toponyms were pointing out presence or absence of specific components of glacio-nival system. They also described features of distribution of snow cover and character of its surface. The place names indicated events related to catastrophic avalanches and glaciers. The positions of the objects with such names were put on thematic maps. The maps reflected development of glacio-nival processes and phenomena in the studied region. It was established that the toponyms reflected not only local features. Some general laws of a glacio-nival complex of the region were found. The ideas on time of appearance of the place names were also expressed.